“Asfalto” (2018)
The objective of this undergraduate work is the feasibility of a project entitled "ASFALTO", which is prepared under the guidelines of the business plan mode, offered by the Cooperativa de Colombia University. This project is an original idea of its creator Katia Álvarez, a student of social communication who is passionate about marketing and the fashion industry.